The return of the king : being the third part of The lord of the rings - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973. (Boston : Houghton Mifflin Co., 1993)
Tells of the opposing strategies of the wizard Gandalf and the evil Sauron as Frodo and Sam struggle to end the great darkness with the Ring of Power.
"Note on the text" / Douglas A. Anderson: pt. 1, p. [v]-viii.
"The text of this edition ... constitutes an authoritative edition"--Pt. 1, t.p. verso.
Includes index.
Young Adult
Keywords: Baggins, Frodo (Fictitious character) -- Fiction; Fantastic fiction, English; Middle Earth (Imaginary place) -- Fiction; Baggins, Frodo (Fictional character) -- Fiction; Middle Earth (Imaginary place) -- Fiction; Fantastic fiction